2005
DOI: 10.1007/s10682-004-2369-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing for resistance of pelagic marine copepods to a toxic dinoflagellate

Abstract: Abstract. With few exceptions, the evolutionary consequences of harmful algae to grazers in aquatic systems remain unexplored. To examine both the ecological and evolutionary consequences of harmful algae on marine zooplankton, we used a two-fold approach. In the first approach, we examined the life history responses of two geographically separate Acartia hudsonica (Copepoda: Calanoida) populations reared on diets containing the toxic dinoflagellate Alexandrium fundyense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 36 publications
(46 reference statements)
6
63
0
Order By: Relevance
“…It is possible that the population of T. longicornis tested in our experiments were resistant to A. fundyense toxins owing to their co-occurrence in the Gulf of Maine. Populations of the copepod Acartia hudsonica from regions exposed to Alexandrium blooms are resistant to adverse effects [32] and can even exhibit enhanced physiological effects such as increased ingestion rate [25] and increased egg production rate [47] when fed A. fundyense versus non-toxic diets. Furthermore, the addition of saxitoxins to a palatable alga diet have even been shown to stimulate feeding in amphipod grazers [48].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the population of T. longicornis tested in our experiments were resistant to A. fundyense toxins owing to their co-occurrence in the Gulf of Maine. Populations of the copepod Acartia hudsonica from regions exposed to Alexandrium blooms are resistant to adverse effects [32] and can even exhibit enhanced physiological effects such as increased ingestion rate [25] and increased egg production rate [47] when fed A. fundyense versus non-toxic diets. Furthermore, the addition of saxitoxins to a palatable alga diet have even been shown to stimulate feeding in amphipod grazers [48].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid evolution of resistance may shape the interactions between zooplankton and toxic algae. Grazer populations that have experienced recurrent HABs can evolve local adaptations to toxic algae (Hairston et al 1999, Colin & Dam 2004). An artificial selection experiment showed that copepods evolved resistance to toxic algae over only 2 to 5 generations (Colin & Dam 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Grazer populations that have experienced recurrent HABs can evolve local adaptations to toxic algae (Hairston et al 1999, Colin & Dam 2004). An artificial selection experiment showed that copepods evolved resistance to toxic algae over only 2 to 5 generations (Colin & Dam 2004). The rapid evolution of resistance may be an important feedback mechanism to minimize the potential deleterious effects of toxic algae on zooplankton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic subpopulations of A. tonsa have been identified in the GOM and along the US Atlantic coast (Caudill & Bucklin 2004, Chen & Hare 2008. Resistance to the toxic dinoflagellate Alexandrium fundyense has been documented for historically exposed populations of the congeneric copepod Acartia hudsonica from Maine and has been induced in naïve populations from the waters off New Jersey (Colin & Dam 2004, Avery & Dam 2007. Given this information, it is highly likely that A. tonsa populations in the GOM may be better evolved to tolerate toxic K. brevis than those in the US SAB.…”
Section: Grazing On Karenia Brevismentioning
confidence: 99%